Joint Stock Company in Corporate Governance - Egamova Zarrina Otabekovna; Tursunov Farkhod Umirzokovich (Scientific Trends, 2024)
The article examines the issue of a joint-stock company in corporate governance. Taking into account the current policy of the Republic of Uzbekistan, the author proposes to improve the legislation of the Republic of Uzbekistan in terms of the structure of the management bodies of JSCs and their competence. According to the author, the low state of activity of joint-stock companies in the economy largely depends on the discrepancy between the dualistic model and business needs.
Keywords: Joint-stock company, structure of management bodies, corporate governance, executive body, competence.